2015
DOI: 10.1159/000438705
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mechanistic Role of Cinnarizine in Modulating Experimentally-Induced Bronchial Asthma in Rats

Abstract: Background/Aims: Calcium influx, inflammatory infiltration, cytokine production, immunoglobulin E activation and oxidative stress play coordinated roles in bronchial asthma pathogenesis. We aim to assess the protective effect of cinnarizine against experimentally induced bronchial asthma. Methods: Bronchial asthma was induced by ovalbumin sensitization and challenge. Rats were allocated into a normal control, an asthma control, a dexamethasone (standard) treatment, and 2 cinnarizine treatment groups. The respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The salicylic acid derivative 5-aminosalicylic acid reduces leukocyte count, the expression of Th2 cytokines, and oxidative stress markers in the BALF from asthmatic mice [401]. Sitagliptin and Cinnarizine also reduce proinflammatory cytokine release and inflammatory infiltration, while restoring GSH and SOD, thus, playing a role attenuating airway inflammation and remodeling through antioxidative stress [402,403]. However, some of the above approaches have failed due to unanticipated side effects.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The salicylic acid derivative 5-aminosalicylic acid reduces leukocyte count, the expression of Th2 cytokines, and oxidative stress markers in the BALF from asthmatic mice [401]. Sitagliptin and Cinnarizine also reduce proinflammatory cytokine release and inflammatory infiltration, while restoring GSH and SOD, thus, playing a role attenuating airway inflammation and remodeling through antioxidative stress [402,403]. However, some of the above approaches have failed due to unanticipated side effects.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The present study explained the administration of cinnarizine causes significant reduction in the expression of immunohistochemistry for colonic cytokines (interleukin-4 and tumor necrosis factor-α) in experimentally induced colitis in rats. Previous study showed that Cinnarizine has anti-inflammatory through itʼs suppressant effect on pro inflammatory cytokines TNF-α, IL-1, and IL-6 release in experimentally-induced bronchial asthma in rats (35).…”
Section: Discussionmentioning
confidence: 95%
“…The study has also shown that administration of cinnarizine significantly reduce the expression of immunohistochemistry for markers of oxidative stress (myeloperoxidase and malondialdehyde) in colonic mucosa of experimentally induced colitis in rats. Studies have suggested that cinnarizine reduces the immune response through inhibition of endothelial oxidative stress and nuclear factor (NF-κB) action (the transcription factor through signaling pathways of phospholipase C and the phosphatidylinositol) (35).…”
Section: Discussionmentioning
confidence: 99%
“… 2016 ), bronchial asthma (Abdel-Fattah et al. 2015a , 2015b ), ulcerative colitis (Ewees et al. 2016 ) and neurodegeneration (Ali et al.…”
Section: Discussionmentioning
confidence: 99%